2018
DOI: 10.28991/cej-0309156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the P-Delta Effect on Collapse Capacity of Adjacent Structures Subjected to Far-field Ground Motions

Abstract: In urban areas, adjacent structures can be seen in any insufficient distance from each other, because of economic and refusal of acquired minimum separation distance according to seismic previsions. Collapse capacity assessment of structures is one of the important objectives of performance-based seismic engineering. The purpose of this study is to consider the pounding phenomenon and P-Delta effect in seismic collapse capacity assessment of structures. For this purpose, 2-, 4-, 6- and 8-story adjacent structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…On the other hand, in order to implement it with an informatic tool and the corresponding code in the context of a nonlinear FEM, some works have been revised [ 19 , 20 , 21 ], as well as others in which nonlinear problems are addressed in various contexts [ 13 , 27 ]. For a stability failure or post-peak behaviour, the arc-length method with load and displacement control is necessary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in order to implement it with an informatic tool and the corresponding code in the context of a nonlinear FEM, some works have been revised [ 19 , 20 , 21 ], as well as others in which nonlinear problems are addressed in various contexts [ 13 , 27 ]. For a stability failure or post-peak behaviour, the arc-length method with load and displacement control is necessary.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the use of an FEM implemented in the appropriate code, it is not linear to be able to address nonlinear incremental method resolution. Details about the FEM’s non-linear formulation can be found in various works [ 19 , 20 , 21 ]. In this case, the beam element is a non-linear Beam2D consisting of a single element.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the plastic hinges of beams and columns may experience a sudden change that may cause an increase in their performance levels. To compare the presence 3-story RC and 5-story steel 0.0 0.077 0.155 3-story RC and 9-story steel 0.0 0.074 0.147 5-story RC and 3-story steel 0.0 0.088 0.176 5-story RC and 5-story steel 0.0 0.129 0.259 5-story RC and 9-story steel 0.0 0.138 0.275 9-story RC and 3-story steel 0.0 0.83 0.166 9-story RC and 5-story steel 0.0 0.125 0.250 9-story RC and 9-story steel 0.0 0.216 0.431 of plastic hinges, moment-rotation hysteresis curve of beam and column of the first floor of the 3-story MRF were calculated according to the modified Ibarra-Krawinkler bilinear-hysteretic model (Kazemi et al 2018a;Lignos and Krawinkler 2010). Then, one record of Pulse-Like (PL) record subsets (Kocaeli Turkey, 8/17/1999, Izmit) suggested by FEMA-P695 (2009) was selected to perform nonlinear time history analysis given that S a (T 1 ) = 1.34 g. To compare the effects of pounding, two models of isolated 3-story steel MRF and 5-story RC MRF were considered, given a separation distance of 0.0.…”
Section: Comparing Moment-rotation Curvesmentioning
confidence: 99%
“…Structural pounding can be categorized as the floor-to-floor pounding (Kazemi et al 2020(Kazemi et al ,2018aCole et al 2010), floor-to-column pounding (Cole et al 2010;Kazemi et al 2018a; Karayannis and Favvata 2005;Efraimiadou et al 2013;Favvata 2017), eccentric or non-eccentric pounding (Cole et al 2010;Leibovich et al 1996;Polycarpou et al 2014), the un-equal weight of adjacent pounding (Kazemi et al 2020;Mohebi et al 2018;Jankowski 2010), and pounding between buildings in series (Skrekas et al 2014;Raheem et al 2019). In particular, Karayannis and Favvata (Karayannis and Favvata 2005) investigated interactions between adjacent reinforced concrete structures with different story heights, where the slab of the shorter structure collides with the columns of the taller one.…”
Section: Introductionmentioning
confidence: 99%
“…Post-earthquake surveys have demonstrated that the pounding configuration plays a key role in the performance of buildings that undergo pounding [9,21], and buildings with a particular configuration are more likely to experience severe damage than others. Configurations that have been identified as more vulnerable include adjacent buildings exhibiting floor-to-column alignments [21][22][23][24], adjacent buildings with significant mass or height differences [22,25], buildings at the end of a row of buildings [21,26], and buildings likely to experience eccentric pounding [9,13,15,21,27]. Therefore, it can be seen that assessing the seismic risk of building portfolios at the urban or regional level with more realism requires the availability of fragility functions that account for the occurrence of these different pounding phenomena.…”
Section: Introductionmentioning
confidence: 99%